2009
DOI: 10.1021/ja904708f
|View full text |Cite
|
Sign up to set email alerts
|

No Confinement Needed: Observation of a Metastable Hydrophobic Wetting Two-Layer Ice on Graphene

Abstract: The structure of water at interfaces is crucial for processes ranging from photocatalysis to protein folding. Here, we investigate the structure and lattice dynamics of two-layer crystalline ice films grown on a hydrophobic substrate, graphene on Pt(111), with low energy electron diffraction, reflection-absorption infrared spectroscopy, rare-gas adsorption/desorption, and ab initio molecular dynamics. Unlike hexagonal ice, which consists of stacks of puckered hexagonal "bilayers", this new ice polymorph consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
177
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(209 citation statements)
references
References 34 publications
(58 reference statements)
28
177
0
Order By: Relevance
“…This result shows that the enhanced hydrophilicity conferred to the surface by the OH groups is lost after formation of the first H 2 O monolayer. This is similar to hydrophobic water layers studied previously on hydrophobic Pt(111) 49 and graphite 50 surfaces as well as on a hydrophilic kaolinite surface 51 . In all these cases, the preferential downward orientation of O-H bonds in the outermost water layers left surfaces devoid of 'dangling H-bonds' which could bind strongly to the next layer of water.…”
Section: Resultssupporting
confidence: 88%
“…This result shows that the enhanced hydrophilicity conferred to the surface by the OH groups is lost after formation of the first H 2 O monolayer. This is similar to hydrophobic water layers studied previously on hydrophobic Pt(111) 49 and graphite 50 surfaces as well as on a hydrophilic kaolinite surface 51 . In all these cases, the preferential downward orientation of O-H bonds in the outermost water layers left surfaces devoid of 'dangling H-bonds' which could bind strongly to the next layer of water.…”
Section: Resultssupporting
confidence: 88%
“…In addition, another work 20 , which was performed without graphene coating, also present the similar hexagon shape on mica via scanning polarization force microscopy. At the same time, other experimental and theoretical works have also clearly pointed out a close match between the lattice constant of the water adlayer and the underlying mica substrate 11,[23][24][25][26] . To further reveal the relative orientation of the water adlayer, the atomic structures are recorded by high-resolution AFM.…”
Section: Experimental Design Overviewmentioning
confidence: 59%
“…Besides, the hydrophobic graphene surface will also guide the water diffusion along the zigzag direction of the C-C bond 26 . Furthermore, previous studies have agreed that no dangling hydrogen bonds are found in the first ice-I h adlayer on mica or the graphene surface 11,24,25 . On the basis of the above analysis, the second and even the third water adlayers should be epitaxially formed at almost zero pressure between mica and the first ice-I h adlayer interface.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations